Asuhan Keperawatan Pada Pasien Post Operasi Sectio Caesarea Atas Indikasi Ketuban Pecah Dini (Kpd) - Nur Alfi Lail; Ramli Efendi; Inka Lestari; Adhin Ahmad Fausi; Arina Tri Noviyani (MEJORA Medical Journal Awatara, 2024)
The 2018 Lower Health Study (Rikesdas) stated that the total number of SC births in Indonesia was 17.6% of 78,736 births. Post-SC mothers do not start breastfeeding on the first day after giving birth because it makes them feel great pain and makes breastfeeding difficult. Another factor that inhibits the formation of breast milk is also influenced by the consumption of post-operative pain relievers. Objective: This research is to determine the description of nursing care for post-operative caesarean section patients with indications of premature rupture of membranes (KPD) in the Mawar ward at Waled Hospital. Method: This type of research is a descriptive method with a case study design. Results: the results of the evaluation at the end of treatment in the diagnosis of acute pain and risk of infection resolved the problem but in the diagnosis of ineffective breastfeeding the problem was partially resolved. Conclusion: The author carried out a comprehensive assessment that was suitable for the conditions of post-operative cesarean section nursing care. The intervention was carried out 2x24 hours with the cooperation of the nurse. The author has taken action in accordance with the nursing plan that has been made.